The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found